Thermoelectric properties of Au and Ti nanofilms, characterized with a novel measurement platform. (2019) - Linseis, V.; Völklein, F.; Reith, H.; Nielsch, K.; Woias, P.
Abstract: Recently we reported on a unique, chip based measurement platform for the complete characterization of the in-plane thermoelectric properties of thin film samples. For the validation of the platform, good thermoelectric materials with a low thermal conductivity and large Seebeck coefficient have already been characterized. In order to check the capability of the platform, with regard to new material classes and applications, we performed measurements of the electrical conductivity σ, thermal conductivity λ and Seebeck coefficient S of two 100 nm Au and Ti thin film samples with considerably larger thermal and electrical transport values. The measured thermoelectric properties of both films show clear size effects, with a remarkably reduced electrical and thermal conductivity as well as Seebeck coefficient, compared to the bulk material, respectively. The Lorenz number of the thin films, which are calculated from the measured electrical and thermal conductivities, are equal to the bulk value, predicted by the Wiedemann–Franz law.